2017
DOI: 10.1007/s12311-017-0858-5
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction Modulation of Low-Frequency Oscillations in the Cerebellar Granule Cell Layer

Abstract: Local field potential (LFP) oscillations in the granule cell layer (GCL) of the cerebellar cortex have been identified previously in the awake rat and monkey during immobility. These low-frequency oscillations are thought to be generated through local circuit interactions between Golgi cells and granule cells within the GCL. Golgi cells display rhythmic firing and pacemaking properties, and also are electrically coupled through gap junctions within the GCL. Here, we tested if gap junctions in the rat cerebella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…The ability to discharge at different rhythms allows them to carry additional information in a more efficient fashion than the average firing rate as it takes the exact spike timing into account (Jirenhed et al, 2017). The cerebellum displays various sorts of rhythmic activities covering both low-frequency (Courtemanche et al, 2002(Courtemanche et al, , 2013Courtemanche & Lamarre, 2005;D'Angelo et al, 2009;Dugu e et al, 2009;Robinson et al, 2017) and high-frequency oscillations (HFO) (Cheron et al, 2004(Cheron et al, , 2014Servais et al, 2005;de Solages et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to discharge at different rhythms allows them to carry additional information in a more efficient fashion than the average firing rate as it takes the exact spike timing into account (Jirenhed et al, 2017). The cerebellum displays various sorts of rhythmic activities covering both low-frequency (Courtemanche et al, 2002(Courtemanche et al, , 2013Courtemanche & Lamarre, 2005;D'Angelo et al, 2009;Dugu e et al, 2009;Robinson et al, 2017) and high-frequency oscillations (HFO) (Cheron et al, 2004(Cheron et al, , 2014Servais et al, 2005;de Solages et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…LFP periods of strong oscillations, in contrast with periods when oscillations were weaker, were identified using spectrograms, calculated using the discrete short-time Fourier transform to evaluate rhythmicity. A multi-parametric algorithm was used to identify oscillatory periods in the 4–12 Hz band of the spectrogram, corresponding with rodent GCL oscillations from other in vivo studies (Hartmann and Bower, 1998 ; O’Connor et al, 2002 ; Dugué et al, 2009 ; Frederick et al, 2014 ; Robinson et al, 2017 ). This algorithm has been used previously to detect and process various rhythmic signals [gamma (Lévesque et al, 2009 ), and theta (Berryer et al, 2016 )].…”
Section: Methodsmentioning
confidence: 99%
“…Intrinsic oscillatory capacities of the GCL local network have been modeled (Maex and De Schutter, 2005 ; Dugué et al, 2009 ; Honda et al, 2011 ; Simões de Souza and De Schutter, 2011 ; Sudhakar et al, 2017 ). For instance, Golgi cell-mediated feedforward and feedback loops (Forti et al, 2006 ; D’Angelo, 2008 ; Dugué et al, 2009 ; Galliano et al, 2010 ), and Golgi-Golgi electrical synapses could be implicated in the rhythm formation (Dugué et al, 2009 ; Vervaeke et al, 2010 ; Simões de Souza and De Schutter, 2011 ; Robinson et al, 2017 ). Further in the circuit, in a limited dataset, we saw that Purkinje cell simple spikes (SSs) can follow the 10–25 Hz GCL rhythm, contrary to complex spikes (Courtemanche et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, intrinsic activity and strong electrical coupling is expected to promote spike synchronization in the GoC network, as observed under anesthesia (van Welie et al, 2016). Previous work has shown that electrically-coupled GoC networks contribute to local field potential (LFP) oscillations in the theta band (~ 8 Hz) (Dugué et al, 2009;Robinson et al, 2017).…”
Section: Implications Of Norepinephrine-mediated Modulation Of Electrmentioning
confidence: 99%